AWARENESS AND ACCEPTANCE OF EPIDURAL LABOR ANALGESIA AMONG PREGNANT WOMEN AT A TERTIARY CARE HOSPITAL - Dhital, Aashish; Maharjan, Deepak; Prasad Adhikari, Shree; Poudel, Sandesh (Journal of Chitwan Medical College, 2024)
Background: Childbirth is widely acknowledged as one of the most intense experiences in a woman’s life. The importance of labor analgesia is often overlooked and its adoption rates remain low in many developing nations. This study aimed to assess the awareness and acceptance of epidural labor analgesia, and to identify any association between demographic variables. Methods: After ethical clearance from Institutional Review Committee, the present cross-sectional study was conducted at Paropakar Maternity and Women’s Hospital from July to September 2023. Two hundred and twenty-seven consecutive pregnant women visiting the Antenatal clinic in hospital were enrolled in the study. Data was collected using paper based structured questionnaires and analyzed by using descriptive and inferential statistical tools in Statistical Package for Social Sciences (SPSS version 24). Results: Of the 227 participants, only 18 (7.9%) were aware of labor analgesia. After the participants were given information about labor epidural analgesia, 173 (76.2%) participants had acceptance for labor epidural analgesia for their current or future pregnancies. Higher education level had significant association with both awareness and acceptance of labor analgesia. Conclusions: Awareness towards labor analgesia although very low, when given information a majority of participants had favorable reception towards it.